(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Hormonal dysfunction is reported among the leprosy patients. Objective: The purpose of the present study was to see the association of testosterone level among male patients presented with lepromatous and borderline leprosy. Methodology: This cross-sectional study was conducted in the Leprosy Hospital, Dhaka, Bangladesh from January to December 2016 for a period of one year. All patients with a known diagnosis of leprosy under follow up at the hospital were included in the study. The serum concentration of testosterone was measured using an enzyme immunoassay technique (ELISA) (DiaMetra, Spello, Italy). Result: A total number of 30 cases of leprosy were recruited for this study. The mean with SD of the study population was 39.20±9.065 years. Among 30 cases of study population 26 cases were lepromatous leprosy patents and the rest 4 cases were Borderline Leprosy patients. The mean with the standard deviation of testosterone level in serum was 6.41±4.756 mg/dL and 4.71±2.396 mg/L in lepromatous leprosy and borderline leprosy respectively (p=0.497). Conclusion: In conclusion there is no statistically significant relationship between leprosy and testosterone; however, lower level of testosterone is found among the study population Bangladesh Journal of Infectious Diseases 2020;7(2):36-39